Comissões Estaduais da Verdade: uma análise comparada - Ferrari, Bruna (Universidade Federal de São Carlos, 2021)
This research aims to employ a comparative analysis of the process of creation, institutionalization and concrete results of the state truth commissions of São Paulo “Rubens Paiva” (CEV-SP) and Rio de Janeiro (CEV-Rio). The research proposes an analysis based on a historical institutionalist perspective and assesses how deputies, CEV members and members of other public institutions made use of available institutional mechanisms to pressure veto-players and guarantee access to resources and autonomy of both commissions. This research also evaluates the impact of these commissions in each state, measuring the CEVs actions towards concrete results, the relationship between their recommendations, the legislative production in ALESP and ALERJ from 2015-2019, and the assessment of people targeted by the military dictatorship of the work of the commissions. The results show that members from each commission employed different strategies: while CEV-Rio sought to establish alliances of partner institutions, CEV-SP based its work on the support of social movements. This difference in approach led to different results. This research seeks to build on the commissions’ institutionalist approaches and defends the importance of the CEVs for the understanding of the modus operandi of the CNV, as well as the innovations promoted in the transitional justice model adopted in Brazil.
State Truth Commissions: a comparative analysis
Keywords: Comissão da verdade; Comissão estadual da verdade; Instituições; Justiça de transição; Direitos humanos; Truth commissions; State truth commission; Institutions; Transitional justice; Human rights; CIENCIAS HUMANAS::CIENCIA POLITICA